"We Swallowed the State as the State Swallowed Us": The Genesis, Genealogies, and Geographies of Genocides in Somalia. Issue 3 (2nd July 2016) - Ingiriis, Mohamed Haji
ABSTRACT: This article theorizes both the causes and the consequences of the state-sponsored genocidal campaigns leveled at the Isaaq clan-group, which can be considered as a case of a "forgotten genocide." Little is academically known about the various uses of political violence by the Somali State with regard to suppressing armed political oppositions and its repercussions. The article assesses the central significance to the militarized state power to reveal ways in which the Mohamed Siad Barre military regime (1969–1991) unleashed state terror on civilians and argues that the legacy left behind by the regime created unforgivable memories for those who were terrorized during the state terror. By transecting both internal and external dimensions, the article explains the roots of the predatory power and selective genocides that culminated in the communal clan convulsions of the 1990s and how the genocidal campaigns in the North led victims of the violence to resort to secession in Somaliland. Using intelligence reports, ethnographic interviews, and visual evidence to ensure triangulation, backed by author's direct observations of living in Somalia at the height of the wars, the article provides a nuanced explanation of the legacies of the military regime. Apart from the contribution to the studies of the postcolonial genocides in Africa, the aim of the article is to open up a discussion and debate about what precipitated Somalia's state collapse to find solutions.